Pemberdayaan Ekonomi Mayarakat Melalui Pengolahan Limbah Kulit Singkong Sebagai Pengganti Bahan Baku Kotak Makanan di Kecamatan Tenayan Raya Kota Pekanbaru - Martilova, Dona; Sari, Neneng Lisma; Nurrahmawati, Novia; Listari, Nia; Saputriyani, Siska; Syahrani, Natasya Lailatul (Universitas Pahlawan Tuanku Tambusai, 2024)
Tenayan Raya District in Pekanbaru City is known as a cassava-producing area with an annual production of 17,499.3 tons. While cassava utilization generally focuses on the tubers and leaves, cassava peels hold significant potential as an alternative raw material for eco-friendly products. This study aims to empower the community through the processing of cassava peel waste into natural-based food containers. The Participatory Rural Appraisal (PRA) approach was employed, encompassing stages of potential identification, production training, and marketing. Results indicate that cassava peel, containing 57% cellulose, can be processed into pulp material that meets the quality standards for food containers. This initiative successfully enhanced the community’s creativity and skills while providing a solution to reduce environmental pollution. Additionally, the program created new business opportunities with the potential to improve local economic income. By actively involving the community and students, this activity not only produced economically valuable products but also fostered the sustainability of innovations based on local resources.